Individual Differences Versus Consumer Readiness Variables Predictive Power Over Internet Banking Adoption in South Africa - C., Aguidissou O.; Shambare, Richard; R., Rugimbana (Journal of Economics and Behavioral Studies, 2018)
Self-service banking technology is gaining recognition globally in spite of its numerous challenges. Debit cards, ATMs and other Self Service Technologies (SSTs) are well received in South African market; however, customers seem cynical about Internet Banking (IB). IB consumer’s adoption patterns frameworks are tested within this paper based on a framework providing for the South African market with the best explanatory power. Thus, investigating consumer readiness (CR) and individual differences (IDs) variables as common groupings usually cited in the literature consumer variables predictive efficacy, provide better understanding of the consumers towards SSTs in South Africa.CR comprises role clarity, ability and motivation (extrinsic and intrinsic), while IDs includes inertia, technology anxiety, need of interaction, previous experience and demographics. This study purposes to identify among IDs and CR variables, which one with greater predictive power on IB adoption in South Africa.Considering this gap within the body of knowledge, in relation with IB adoption behaviour among the South African consumer is therefore the present article primary objective. Consumer’s individual differences (technology anxiety and education variables specifically) as exogenous variables, through a large sample size (n=1516), descriptive quantitative analysis, were found in context of South African market with greatest predictive power for IB adoption by comparison over consumer readiness. In South Africa particularly for marketers, these findings therefore are a set of relevant keys that can be useful in promoting IB adoption.